2022
DOI: 10.1111/jog.15368
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurement of vaginal thickness: Relation to menopausal status and genitourinary syndrome of menopause

Abstract: Objective: To compare the total vaginal wall thickness (TVT) and total mucosal thickness (TMT) measurements of premenopausal and postmenopausal women measured by ultrasonography and to determine the association of these measurements to findings and symptoms of genitourinary syndrome of menopause Methods: Healthy volunteers, 80 postmenopausal and 80 premenopausal, were included. Ultrasonographic TVT and TMT measurements, vaginal health index (VHI) scores and pH values were recorded. The daily impact of vaginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some authors have advocated measuring the total vaginal wall thickness using transabdominal ultrasound in the sagittal plane using a full bladder approach. [5][6][7] The potential limitation of this approach is that full bladder distension could affect vaginal wall thickness by provoking an artificial thinning and due to lower resolution compared to the transvaginal route, it could be difficult to differentiate the bladder wall from the vaginal wall. Furthermore, no studies assessing the repeatability of this measurement have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have advocated measuring the total vaginal wall thickness using transabdominal ultrasound in the sagittal plane using a full bladder approach. [5][6][7] The potential limitation of this approach is that full bladder distension could affect vaginal wall thickness by provoking an artificial thinning and due to lower resolution compared to the transvaginal route, it could be difficult to differentiate the bladder wall from the vaginal wall. Furthermore, no studies assessing the repeatability of this measurement have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…As vaginal wall thinning is a real phenomenon in the GSM, ultrasound measurement of vaginal wall thickness has been proposed as a potential biomarker of vaginal health. In fact, some authors have advocated this measurement using ultrasound 5–11 . However, we observed that there is no standardized approach for measuring vaginal wall thickness.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this manuscript, we aimed to evaluate a novel methodology for the measurement of vaginal wall thickness utilizing a transvaginal biplanar ultrasound probe. For the measurement of vaginal wall thickness (VWT), various ultrasound techniques have been proposed in the literature [ 3 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], both transabdominal and transvaginal and both 2D and 3D at high frequency. Panayi first described a transvaginal US technique to measure the thickness of the vaginal wall at various anatomical sites, including the bladder neck, anterior and posterior fornix, and rectum [ 21 ].…”
Section: Discussionmentioning
confidence: 99%